2021
DOI: 10.1109/ojsp.2021.3084541
|View full text |Cite
|
Sign up to set email alerts
|

A Tensor Framework for Multi-Linear Complex MMSE Estimation

Abstract: Tensors are higher order generalization of vectors and matrices which can be used to describe signals indexed by more than two indices. This paper introduces a tensor framework for minimum mean square error (MMSE) estimation for multi-domain signals and data using the Einstein Product. The framework addresses both proper and improper complex tensors. The multi-domain nature of tensors has been harnessed to provide an augmented representation of improper complex tensors to account for covariance and pseudo-cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…where N ∈ C J 1 ו••×J M represents the order M received noise tensor. The conventional MIMO matrix model can be seen as a specific case of (3) where the input and output are order 1 tensors (vectors) and the channel is an order 2 tensor (matrix) [10]. In such a case, the Einstein product between the channel and the input by definition reduces to standard matrix multiplication.…”
Section: A Generic System Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…where N ∈ C J 1 ו••×J M represents the order M received noise tensor. The conventional MIMO matrix model can be seen as a specific case of (3) where the input and output are order 1 tensors (vectors) and the channel is an order 2 tensor (matrix) [10]. In such a case, the Einstein product between the channel and the input by definition reduces to standard matrix multiplication.…”
Section: A Generic System Modelmentioning
confidence: 99%
“…A detailed derivation of ( 18) can be found in [19]. An application of such a tensor-based receiver in a MIMO OFDM system is considered in [10] where a comparison with per sub-carrier estimation which ignores the inter-carrier interference terms for estimation is presented. It is shown that as interference from other sub-carriers becomes dominant, the performance of per sub-carrier receiver deteriorates significantly, while the tensor receiver's is significantly better since it makes use of the interference terms for data estimation.…”
Section: Tensor-based Receiver Designsmentioning
confidence: 99%
See 3 more Smart Citations